Analisis Kenyamanan Termal pada Bangunan Coffe Shop (Studi Kasus: Ghathaf Kafe Kecamatan Syamtalira Aron) - Mawardi, R; Safyan, A; Nurhaiza (Cered Indonesia Institute, 2024)
As one of the largest coffee-producing regions in Indonesia, this is one of the factors for the rapid development of cafes in the Aceh area, especially in North Aceh district with various shapes and models. Besides being one of the places to enjoy coffee, the cafe is also one of the places to gather and relax, so from this some important aspects must be considered both in terms of form and comfort. Thermal comfort is a process that involves two aspects of comfort, namely psychological and physical aspects. The author is interested in examining one of the coffee shops that are quite crowded visited, namely Gathaf Cafe. This cafe consists of 2 floors with reinforced concrete construction. The selection of building objects is assessed from the materials used, where almost the entire building envelope uses spandex material. The influence of the environment around the building also affects the thermal in the Ghathaf cafe building which is in a public location with a dense level of activity. In conducting this research the method used is quantitative research as the main method and qualitative methods as a supporting method. the level of thermal comfort at Ghathaf Coffe Premium still does not meet the thermal comfort standards of ASHRAE-55, where the results obtained after testing the CBE Thermal Comfort Tool software with PMV and PPD methods the value that comes out for each measurement point on average gets sensation too warm (slightly warm) with an acceptance limit of 80% and an acceptance limit of 90%. This is understandable because Ghathaf Coffee Premium is using natural ventilation as a source of thermal comfort support. Thermal control of the building is done by maximizing the wide natural materials, which utilizes the building without passive wall envelope so that thermal control is optimized on good natural ventilation into the cafe.